2022
DOI: 10.1109/access.2022.3188852
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Digital Human Agent Service With Deep Learning Based-Face Recognition

Abstract: This study proposes a framework for an intelligent agent information service using digital human and deep learning technology. The framework can recognize the identity of individuals using facial features and provide personalized services through a digital human. The personalized service is defined by a relevance graph based on personal data collected in advance. The proposed system can continuously evolve to recommend customized services using relevance graphs and dynamic data processing, gradually become mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…The authors found some prominent technologies that gained significant importance over this period. We also compared our findings with other studies, showing that facial recognition technology, capture-based and synthesis motion, rendering technology, and "Digital Human Modeling" based on virtual reality are all topics of interest to scholars [71][72][73][74]. However, the "Intelligence-Driven" module is hardly mentioned in previous research, possibly because there has been limited exploration of modules in the practical dimension.…”
Section: Discussionmentioning
confidence: 75%
“…The authors found some prominent technologies that gained significant importance over this period. We also compared our findings with other studies, showing that facial recognition technology, capture-based and synthesis motion, rendering technology, and "Digital Human Modeling" based on virtual reality are all topics of interest to scholars [71][72][73][74]. However, the "Intelligence-Driven" module is hardly mentioned in previous research, possibly because there has been limited exploration of modules in the practical dimension.…”
Section: Discussionmentioning
confidence: 75%
“…availability attack in federated learning). Rapidly however, this attack channel became prominently featured as an integrity vulnerability in the backdoor attack literature [31], [70], [79]- [89]. In this context, attacks are targeted (i.e.…”
Section: ) Data Collectionmentioning
confidence: 99%
“…Penelitian ini memiliki manfaat yang signifikan, terutama dalam meningkatkan efisiensi serta kepuasan pelanggan, dan menciptakan hal yang berbeda dalam pemesanan menu dan menjadi sesuatu yang menari untuk pelanggan [10]. Dengan menggunakan Teknologi kecerdasan buatan, Computer Vision dangan metode CNN, Penelitian ini akan menciptakan sesuatu pengalaman pelanggan yang lebih mudah dan cepat dalam memesan dan membayar menggunakan sistem digital dioutlet dengan pelayanan secara virtual dalam menggunakan teknologi kecerdasan buatan [11]. Hasil pengembangan ini memberikan hasil positif untuk pelayanan dan mempersingkat waktu tunggu pelanggan setelah pemesanan dan waktu pembayaran yang mudah, dapat memberikan kontribusi bagi perkembangan industri makanan dan minuman serta pengembangan teknologi dimasa depan [12].…”
Section: Pendahuluanunclassified